2019
DOI: 10.26434/chemrxiv.8053385.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solid-like Ordering of Imidazolium-Based Ionic Liquids at Rough Nanostructured Oxidized Silicon Surfaces

Abstract: The investigation of ionic liquids (ILs) confined in a solid porous matrix is of particular interest considering that these substances are increasingly used as electrolyte in devices employing nanostructured nanoporous materials for the electrodes. Furthermore, the confinement of the ILs into a porous matrix would allow overcoming the difficulties of its packaging, leakage and portability. In order to support applications, a deeper understanding of the interaction of ILs with the nanoporous solid material and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A robust experimental evidence of extended, highly packed layering in thin IL films, in some cases markedly solid-like in character, supported on metallic and insulating solid surfaces, have been collected in the last ten years [31,38,39,67,[86][87][88][89][90][91][92]. The ordered structures typically extend in the direction perpendicular to the substrate by several nanometers, and in some cases tens of nanometers.…”
Section: Ordering and Solid-like Properties Of Interfacial Nanoconfinmentioning
confidence: 99%
See 1 more Smart Citation
“…A robust experimental evidence of extended, highly packed layering in thin IL films, in some cases markedly solid-like in character, supported on metallic and insulating solid surfaces, have been collected in the last ten years [31,38,39,67,[86][87][88][89][90][91][92]. The ordered structures typically extend in the direction perpendicular to the substrate by several nanometers, and in some cases tens of nanometers.…”
Section: Ordering and Solid-like Properties Of Interfacial Nanoconfinmentioning
confidence: 99%
“…In Ref [87] we recently reported the results of a systematic characterization, performed by AFM, of the morphological and mechanical properties of [Bmim][NTf 2 ] thin films supported on a rough nanostructured oxidized silicon surface produced by SCBD. We observed that the high roughness and nanoscale porosity of the oxidized silicon film did not prevent the formation of solid-like IL domains, even when they are surrounded by the IL in the liquid phase ( Figure 7).…”
Section: Ordering and Solid-like Properties Of Interfacial Nanoconfinmentioning
confidence: 99%
“…Besides, 2D IR spectroscopy of RTILs thin films also presents a dynamical molecular behaviour that fully ressembles the one of a supercooled liquid [31]. The mechanical measurements performed on solid-like, fully crystallized, interfacial systems obtained from drop-casting of RTILs/methanol solution provides a measure of the Young modulus E * ≈ 60 MPa [32]. Here, we obtain a value that is about 2 orders of magnitude smaller and further points towards the glassy nature of the nanoconfined RTILs.…”
Section: Transition To Glassy Response In Confinementmentioning
confidence: 99%
“…Experimentally, skillfully exploiting surface roughness can considerably optimize the capacitance in electric double layer (EDL) capacitors. 70−72 For example, Borghi et al 71 have shown that the rough and porous electrode surfaces can not only boost the active surface area but also specifically confine IL at the solid/liquid interface. Furthermore, the simulations proposed by Vatamanu et al 72 have also confirmed that the IL electrolytes can generate larger capacitances at the nanoporous electrodes composed of two prismatic faces of graphite with rough surfaces than those with flat surfaces.…”
Section: Resultsmentioning
confidence: 99%